ANALISIS TINGKAT PELAYANAN OPTIMAL PADA RUMAH MAKAN MIE AYAM MAS YUDI JL. SAGAN KIDUL NO 20 YOGYAKARTA - Handoko, Wina Meilia Waspadiana; Widjojo, A.M Rosa (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2013)
Tis study aimed to analyze the cost of the queue, facility costs and optimal service levels at Rumah Makan Mie Ayam Mas Yudi Jl Sagan Kidul 20 Yogyakarta. Te data used are primary data, which is obtained directly by observation and direct counts the number of consumers who come in Rumah Makan Mie Ayam Mas Yudi Jl Sagan Kidul 20 Yogyakarta at a given time. Data analysis method used is queuing theory. Te results of the calculation found the average arrival rate of customers is 8.133 people per 10 minutes. Tus the arrival time of customers for each minute is 1 / Î» or 10/8, 133 = 1.23 or every 1.23 minutes on average come one customer. Te majority of visitors of Rumah Makan Mie Ayam Mas Yudi are students, and therefore used the sample student staf salaries Atma Jaya Yogyakarta University of Rp5000, - per hour as a component of cost of the queue to compute optimal service levels in this study. Ten the opportunity cost for 10 minutes is Rp833, 33 (Rp5000 / 6). Facility costs that arise because organizations must conduct additional investment in order to increase the service level of service facility that is Rp 2.093 Î¼ increases, 93 per 10 minutes. optimal Î¼ is 9.93 per 10 minutes. Overall results of this study indicate that in order to minimize costs, both costs to be incurred by the service providers and the opportunity cost to be borne by the customer. Terefore, the average service time (service time) to be given to each customer is 1.007 minutes (10/9, 93).Keywords: queuing theory, arrival rate, queuing costs, facility costs, optimal service levels